Design and Optimization of a CD4 Primer for Quantitative Real-Time PCR (qRT-PCR) - Oktavia, Puji; Eka Putra, Andani; Aliska, Gestina; Rofinda, Zelly Dia; Elvira, Dwitya; Arisanty, Dessy (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Quantitative real-time polymerase chain reaction (qRT-PCR) is being explored as an affordable alternative to flow cytometry for monitoring CD4+ T lymphocytes in HIV-infected patients, but detailed design and validation of CD4-specific primers are rarely reported. To design a CD4-specific primer-probe set for qRT-PCR, assess its in silico specificity, and determine the optimal annealing temperature. A forward primer, reverse primer, and hydrolysis probe targeting CD4 transcript were designed from published CD4 gene sequences. Specificity was evaluated using NCBI Primer-BLAST against the Human mRNA RefSeq database. Optimal annealing temperature was determined using an 8-point thermal gradient (54.0-66.0°C) on a Bio-Rad CFX96 system with SensiFAST™ Probe No-ROX chemistry, comparing Cq values across the gradient. Results: Primer-BLAST confirmed specificity of the forward (20nt, Tm 57.42°C, GC 50.00%) and reverse (24nt, Tm 57.69°C, GC 41.67%) primers, with low self-complementarity (3.00 and 2.00) and no 3' self-complementarity. Cq values were tightly clustered (23.25-23.76) across the gradient; with the lowest Cq (23.25) at 54.8°C. The CD4-specific primer-probe set showed confirmed specificity and robust tolerance across a wide annealing temperature range, with an optimum of 54.8°C, supporting its use as a foundational tool for CD4+ T lymphocyte monitoring where flow cytometry is inaccessible.